Treatment Approaches to Chronic Lymphocytic Leukemia With High-Risk Molecular Features - van der Straten, Lina; Hengeveld, Paul J.; Kater, Arnon P.; Langerak, Anton W.; Levin, Mark-David (Frontiers in Oncology, 2021)
The clinical course of chronic lymphocytic leukemia (CLL) is highly variable. Over the past decades, several cytogenetic, immunogenetic and molecular features have emerged that identify patients suffering from CLL with high-risk molecular features. These biomarkers can clearly aid prognostication, but may also be capable of predicting the efficacy of various treatment strategies in subgroups of patients. In this narrative review, we discuss treatment approaches to CLL with high-risk molecular features. Specifically, we review and provide a comprehensive overview of clinical trials evaluating the efficacy of chemotherapy, chemoimmunotherapy- and novel agent-based treatments in CLL patients with TP53 aberrations, deletion of the long arm of chromosome 11, complex karyotype, unmutated IGHV, B cell receptor stereotypy, and mutations in NOTCH1 or BIRC3. Furthermore, we discuss future pharmaceutical and immunotherapeutic perspectives for CLL with high-risk molecular features, focusing on agents currently under investigation in clinical trials.